Study of electrochromic characteristics in the near-infrared region of electrochromic devices based on solution-processed amorphous WO3 films. (December 2018) - Ding, Jingjing; Liu, Zhen; Wei, Aixiang; Chen, T.P.; Zhang, Haiyan
Abstract: In this paper, tungsten oxide (WO3 ) thin films and hybrid polyelectrolyte have been synthesized by solution-based processes to form solid-state electrochromic devices (ECDs). Electrochromic properties of the ECDs have been investigated, focusing on the near-infrared (NIR) region of the light spectrum. By optimizing the applied impulse voltage and WO3 film thickness, a coloration efficiency of 78.8 cm 2 /C has been achieved in the ECD under the impulse voltage of ± 2.5 V. In addition, at the same voltage, the response time of 2.5 s and 15.8 s was obtained for bleaching and coloring, respectively. The fast switching between colored and bleached states is due to the porous structure of solution-processed WO3 films that facilitates injection/release of Li ions. Stable current-time profiles have been obtained during cyclic measurements with alternating impulse voltages within 6 × 10 3 s, indicating excellent reversibility in the ECDs. The solid-state ECDs based on WO3 films are promising to be used in applications requiring NIR-related optical modulation such as smart windows.